REKONSTRUKSI PEMBELAJARAN EKONOMI ISLAM PADA PERGURUAN TINGGI AGAMA ISLAM (Antisipasi Pengembangan ke Depan) - SYAPARUDDIN, SYAPARUDDIN (At-Taradhi Jurnal Studi Ekonomi, 2012)
This article discusses the need to reconstruct Islamic economy curriculum in Islamichigher education. Since about ten years ago, Islamic economy has become a special concentrationin many campuses but the procces of searching its most proper study model is still ongoing. Tofulfill the markets demands, both state and private campuses need to reconstruct their studymodel of Islamic economy by stressing the combination of Sharia and economics. This will be-come a basis for the students to produce some creative ways to develop Islamic economy accord-ing to societys needs. The exponents of Islamic economy and the staff of departments of Islamiceconomy in higher education must formulate an instruction pattern or a standard curriculum forIslamic economy. Most importantly, the curriculum must be relevant to todays market. Bydoing so, the alumni of the departments of Islamic economy will gain an enterpreneurship ethos,to be the masters on their own.